(untitled) (Bangladesh Journal of Plastic Surgery, 2013)
In this article we report one case of lipoma of the penis in a twenty three years old young male. This site of lipoma is rare. A case of a young male patient who consulted for removal of a penile lump is presented. The small, regular, wellcircumscribed pedunculated tumor localized on the ventral aspect of the penis was excised. The histopathological analysis showed a benign lipoma. A review of the literature showed lipoma of the penis to be very uncommon. For this reason, we were prompted to report this case. DOI: http://dx.doi.org/10.3329/bdjps.v3i1.15003 Bangladesh Journal of Plastic Surgery 2012, 3(1): 24-25